Characteristics of Neck Pain in Medical Students of Muhammadiyah Jakarta University Class of 2019 After Online Class for One Semester - Kasmi, Raras Sakti Mulya; Hamzah, Zaini (Talenta Universitas Sumatera Utara, 2023)
Introduction: Neck pain is a very common complaint in everyday life. Neck pain is a multifactorial disease with many associated risk factors. In population studies, 20-60% of women and 15-40% of men have experienced neck pain. Neck pain is a health problem that can develop and interfere with a person daily activity. Method: This research is a descriptive analytic survey research, which aims to know about neck pain of the students of the Medical Education Study Program Class of 2019. approach used in this study is